2,5-dimethylcelecoxib improves immune microenvironment of hepatocellular carcinoma by promoting ubiquitination of HBx-induced PD-L1 - Zhanfei Chen; Yiyin Chen; Lirong Peng; Xiaoqian Wang; Nanhong Tang (Journal for ImmunoTherapy of Cancer)
Background 2,5-dimethylcelecoxib (DMC) is a targeted inhibitor of microsomal prostaglandin E synthase-1 (mPGES-1), a key enzyme in the PGE2 synthesis pathway of inflammatory mediators. Previous studies have confirmed that DMC can inhibit the growth of hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). However, it is not known whether DMC is involved in the changes of tumor immune microenvironment.Methods In this study, we explored the effects of DMC on HBV-related HCC immune microenvironment, and deeply analyzed its unique effect and mechanism on programmed death receptor 1 (PD-1)/and its ligand 1 (PD-L1) pathway.Results Clinical hepatoma tissues detection showed that compared with non-virus-related HCC, the level of CD8 of HBV-related HCC was significantly lower, while the levels of PD-L1 and CD163 were higher. In vivo experiments indicated that DMC could increase the level of tumor infiltrating CD8+ T cells in hepatitis B virus X (HBx) (+) hepatoma cells implanted mouse models, and inhibit the expression of PD-L1 and CD163 in tumor tissues. DMC combined with atezolizumab had more significant antitumor effect and stronger blocking effect on PD-1/PD-L1 pathway. Mechanism studies have shown that DMC can promote ubiquitin degradation of HBx-induced PD-L1 protein in HCC cells by activating adenosine 5′-monophosphate-activated protein kinase pathway. Further experiments confirmed that this process was mainly mediated by E3 ligase RBX1.Conclusions Our results uncover a role for DMC in promoting HBV-related HCC immune microenvironment, which not only enrich the relationship between inflammatory factors (mPGES-1/PGE2 pathway) and immunosuppression (PD-L1), but also provide an important strategic reference for multitarget or combined immunotherapy of HBV-related HCC.